2018
DOI: 10.1249/mss.0000000000001442
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Compensations due to Chronic Ankle Instability during Landing and Jumping

Abstract: CAI patients seemed to use a hip-dominant strategy by increasing the hip extension moment, stiffness, and eccentric and concentric power during landing and jumping. This apparent compensation may be due to decreased capabilities to produce sufficient joint moment, stiffness, and power at the ankle and knee. These differences might have injury risk and performance implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 42 publications
0
38
2
Order By: Relevance
“…150 These landing strategies were associated with proximal kinematic and kinetic changes at the knee and hip. 149,151,152 Reduced fibularis longus muscle activation among patients with CAI has been seen in some studies, 150 but conflicting results 152 showed increased fibularis activation. Increased activation of the gluteus maximus muscle before initial contact has also been demonstrated in patients with CAI.…”
Section: Motor-behavioral Impairmentsmentioning
confidence: 99%
“…150 These landing strategies were associated with proximal kinematic and kinetic changes at the knee and hip. 149,151,152 Reduced fibularis longus muscle activation among patients with CAI has been seen in some studies, 150 but conflicting results 152 showed increased fibularis activation. Increased activation of the gluteus maximus muscle before initial contact has also been demonstrated in patients with CAI.…”
Section: Motor-behavioral Impairmentsmentioning
confidence: 99%
“…The aforementioned hip-dominant gait strategy has also been documented in patients with CAI during landing and cutting. 34,45 They appear to rely more on the hip joint by increasing hip-joint stiffness, hip-flexion angle, hip-extension moments, and eccentric and concentric joint powers during jump landing and cutting to compensate for reduced ankle-joint stiffness, plantar-flexion moments, and eccentric and concentric powers. 34,45 One possible explanation for this hip-dominant movement strategy in patients with CAI may be sensorimotor deficits in proprioception, motorneuron pool excitability, reflex reactions, muscular strength, and postural control, as suggested by Hertel.…”
Section: Hip-dominant Gait Strategy (Kinetic and Kinematic)mentioning
confidence: 99%
“…34,45 They appear to rely more on the hip joint by increasing hip-joint stiffness, hip-flexion angle, hip-extension moments, and eccentric and concentric joint powers during jump landing and cutting to compensate for reduced ankle-joint stiffness, plantar-flexion moments, and eccentric and concentric powers. 34,45 One possible explanation for this hip-dominant movement strategy in patients with CAI may be sensorimotor deficits in proprioception, motorneuron pool excitability, reflex reactions, muscular strength, and postural control, as suggested by Hertel. 18 We believe that these sensorimotor deficits, along with mechanical deficits (ie, ligament laxity, arthrokinematic restrictions, and osteokinematic restrictions), could result in a maladaptive movement strategy, regardless of the task, 26 via the spinal or supraspinal sensorimotor pathways.…”
Section: Hip-dominant Gait Strategy (Kinetic and Kinematic)mentioning
confidence: 99%
“…[13][14][15] More specifically, proximal-segment alterations and reduced ankle neuromuscular control were observed when individuals who developed CAI performed dynamic movements, such as jump landings and side-cutting tasks. [15][16][17][18] This indicates that the chronically unstable ankle is unable to effectively attenuate impulse loads imposed on the ankle complex and results in an intralimb redistribution of impact-force attenuation in which greater reliance is placed on the proximal joints to protect the injured ankle during dynamic movements. 16,18 Researchers 13,15,19 have suggested that longitudinal alterations to spinal-and supraspinal-level motor-control strategies, which arise from the sensorimotor constraints of CAI, are likely an underlying mechanism in developing CAI and recurrent lateral ankle sprains.…”
mentioning
confidence: 99%
“…[15][16][17][18] This indicates that the chronically unstable ankle is unable to effectively attenuate impulse loads imposed on the ankle complex and results in an intralimb redistribution of impact-force attenuation in which greater reliance is placed on the proximal joints to protect the injured ankle during dynamic movements. 16,18 Researchers 13,15,19 have suggested that longitudinal alterations to spinal-and supraspinal-level motor-control strategies, which arise from the sensorimotor constraints of CAI, are likely an underlying mechanism in developing CAI and recurrent lateral ankle sprains. Therefore, an assessment of lower limb movement dynamics during sport-specific tasks that pose substantial risks for LAS in individuals with CAI is warranted.…”
mentioning
confidence: 99%